2021
DOI: 10.3892/ijmm.2021.4864
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial infection of COVID‑19: A new challenge for healthcare professionals (Review)

Abstract: Nosocomial infections, also known as hospital-acquired infections, pose a serious challenge to healthcare professionals globally during the Coronavirus disease 2019 (COVID-19) pandemic. Nosocomial infection of COVID-19 directly impacts the quality of life of patients, as well as results in extra expenditure to hospitals. It has been shown that COVID-19 is more likely to transmit via close, unprotected contact with infected patients. Additionally, current preventative and containment measures tend to overlook a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
66
1
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 86 publications
1
66
1
9
Order By: Relevance
“…According to a previous survey in Japan, 52% of the staff infected were nurses [ 40 ]. In the three hospitals in our study, when an infection is found in a ward, the nurses in close contact with the relevant people are isolated immediately, which means that ward duties must be performed on a limited shift, increasing the workload per person [ 18 , 30 , 43 , 45 , 46 , 48 , 49 ]. In addition, when shift changes required support from other departments, the work was unfamiliar as were the new members, which increased stress [ 31 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a previous survey in Japan, 52% of the staff infected were nurses [ 40 ]. In the three hospitals in our study, when an infection is found in a ward, the nurses in close contact with the relevant people are isolated immediately, which means that ward duties must be performed on a limited shift, increasing the workload per person [ 18 , 30 , 43 , 45 , 46 , 48 , 49 ]. In addition, when shift changes required support from other departments, the work was unfamiliar as were the new members, which increased stress [ 31 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the three hospitals in our study, when an infection is found in a ward, the nurses in close contact with the relevant people are isolated immediately, which means that ward duties must be performed on a limited shift, increasing the workload per person [ 18 , 30 , 43 , 45 , 46 , 48 , 49 ]. In addition, when shift changes required support from other departments, the work was unfamiliar as were the new members, which increased stress [ 31 , 49 ]. The burden on the remaining nurses should be reduced as much as possible by actively recruiting nurses from outside the organization whenever possible.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its global health impact, COVID-19 has alarmed the healthcare community about the danger and harm of nosocomial infections. Nosocomial infection associated with COVID-19 has been identified and reported by several healthcare facilities across the world [ 2 ] . Due to the lack of adequate awareness about COVID-19 during the early stages of the pandemic, some healthcare workers also got infected [ 3 ] .…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare workers account for 3% of the world's population and also account for 14% of all cases of infection 8 . Second, nosocomial infection of COVID-19 directly impacts the quality of medical care and also the safety of the patients 9 . Patients with other diseases are likely to face more severe consequences after acquiring COVID-19 infection, with an increased risk of mortality 10 .…”
Section: Introductionmentioning
confidence: 99%
“…These frameworks of competencies fail to meet the requirements of HIPC practitioners, brought forth by the new COVID-19 crisis. Moreover, new technologies are widely being used in the medical eld presently, which have played a crucial role in the prevention and control of COVID-19 in various ways, albeit these models have failed to keep up with the present day needs and requirements 9,21 .…”
Section: Introductionmentioning
confidence: 99%